Bibsy Cross and the bike-a-thon - Scanlon, Liz Garton; Ho, Dung (Alfred A. Knopf, 2024)
When precocious eight-year-old Bisby's library hosts a bike-a-thon to raise money to buy books, she is determined to win the fundraiser.
Ages 7-10.
Grades 2-3.
Keywords: Bicycles and bicycling -- Fiction; Fund raising -- Fiction; Libraries -- Fiction